(untitled) (Sinología hispánica. China Studies Review, 2019)
A gifted linguist, diplomat, and negotiator, Yu Jing (1000-1064) is uniquely qualified among Northern Song officials in his extensive knowledge of Khitan language and culture. At a time when Liao-Song relationship was at its most contentious, the advantage of having an official who could communicate fluently in both languages cannot be overstated. However, according to official history, not only did his bilingualism not endear him to the court, it aroused constant suspicion and led to his eventual impeachment, which occurred after he composed a poem in the Khitan language and presented it to the Emperor of the Liao State as a token of gratitude. The purpose of this paper is to reexamine the cause of Yu Jing’s indictment in the context of political machination. By contextualizing his composition of the Poem in the Language of the Barbarian and subsequent impeachment within the politics of the court, my goal is to supplement, even challenge, our above conventional acceptance of xenophobia as the sole cause of Yu’s downfall. In doing so, I hope to point out the potential flaw of our current understanding of Song diplomacy as guilelessly dictated by its inferiority complex and0xenophobic sentiments.